Scalable synthesis of wrinkled mesoporous titania microspheres with uniform large micron sizes for efficient removal of Cr(vi). Issue 9 (9th February 2018) - Yu, Zhikai; Gao, Xingmin; Yao, Yan; Zhang, Xiangcheng; Bian, Guo-Qing; Wu, Winston Duo; Chen, Xiao Dong; Li, Wei; Selomulya, Cordelia; Wu, Zhangxiong; Zhao, Dongyuan
Abstract : Scalable synthesis of wrinkled mesoporous TiO2 microspheres with uniform large micron sizes is achieved. They show excellent performance for removal of Cr(vi ). Abstract : Aerosol-assisted methods possess a strong capability for synthesis of titania (TiO2 ) microspheres. For dynamic separation applications, rough TiO2 microspheres with uniform large micron sizes, high external-surface-area-to-volume ratios, high surface areas, uniform mesopores and abundant hydroxyl groups are desirable. Herein, we demonstrate the combination of evaporation induced self-assembly (EISA) with a microfluidic-jet spray drying process for scalable synthesis of novel mesoporous TiO2 materials with the above-mentioned properties for Cr(vi ) removal under both static and dynamic conditions. The TiO2 materials are spherical with uniform large micron sizes (∼45 μm). They possess wrinkled surfaces and thus have high particle external-surface-area-to-volume ratios. They show high surface areas (22–138 m 2 g −1 ), large pore volumes (0.15–0.27 cm 3 g −1 ) and uniform mesopores (5.2–20.7 nm). They carry abundant surface Ti–OH groups due to the presence of oxygen vacancies and the Ti 3+ valence state. Several experimental parameters, such as drying and calcination temperatures, are varied, leading to TiO2 samples with tunable surface areas and mesopore sizes. They can be adopted as batch sorbents for removal of Cr(vi ) in water with fast adsorption rates, large capacities and pH-dependent adsorption behavior. Part of the adsorbed Cr(vi ) can be reduced to Cr(iii ) in acidic solutions. The influences of adsorbent properties on adsorption performance are elucidated. Moreover, their uniform large micron sizes make them excellent fillers for efficient separation of Cr(vi ) in dynamic flows with similar performance to that under static conditions, as well as easy regeneration and high cycling stability. Their adsorption performance under flowing conditions is much better than those of commercial TiO2 nanoparticles and mesoporous TiO2 materials prepared by a conventional EISA method, which make them very attractive for practical dynamic separation applications.